PERAN SISTEM INFORMASI AKUNTANSI BERBASIS MOBILE BAGI PENINGKATAN KINERJA UMKM - Ni Kadek Sinarwati; Edy Sujana; Nyoman Trisna Herawati (Faculty of Economics and Business, Universitas Warmadewa, 2019)
The presence of a mobile-based Accounting Information System (AIS) for MSMEs is expected to play a role in improving the performance of MSMEs. This study aims to analyze the role of mobile-based AIS for MSMEs. The type of research is qualitative descriptive. The role measurement is done by measuring the performance of MSMEs before and after using AIS in managing their business. AIS plays a role if there are significant differences in MSMEs performance. MSMEs administrative management data is collected by observation, interviews and in-depth interviews. The sample is determined by the quota method and purposive sampling. The data analysis technique used is qualitative descriptive analysis. The results showed that mobile-based AIS plays a role in improving the business performance of MSMEs with indicators after the implementation of AIS MSMEs business administration is more neat and organized than before the implementation of SIA, after the implementation of mobile-based AIS, MSMEs was able to prepare its business financial statements. The ability of MSMEs to compile financial statements has implications for the ease of MSMEs getting financial assistance from banks.